Hubungan Stres dengan Nyeri pada Pasien Dispepsia Ruang Nusa Indah di RSU Bhakti Asih Tangerang Bulan Agustus - Oktober 2024 - Juni Riani; Ayu My Lestari; Rizki Halifah Ashri; Nurdewi Sulymbona (Jurnal Rumpun Ilmu Kesehatan, 2024)
Dyspepsia is a collection of symptoms in the form of discomfort in the upper abdomen, pain, nausea, and vomiting as well as the stomach feels full quickly when eating and feels bloated. One of the factors that causes dyspepsia is psychosocial factors, namely stress. The purpose of the study was to determine the Relationship between Stress and Pain in Dyspepsia Patients in the Nusa Indah Room at Bhakti Asih Hospital, Tangerang, August - October 2024. Quantitative research method with a Cross Sectional approach. The research sample was 53 respondents using a purposive sampling technique. The stress measurement instrument used the DASS-42 questionnaire and Pain measurement. Data were analyzed using the chi-square test. The results showed that the majority of Anemia was Severe (93.8%) and the quality of life variable was in the Good category (76.9%). Based on statistical tests using the Spearman rank correlation test, a significance level of p-value = 0.000 was obtained with an OR value of 0.548, which means that the relationship between these two variables was moderate and inversely related. Conclusion, there is a relationship between stress levels and pain in patients with dyspepsia in the Nusa Indah Room at Bhakti Asih Hospital, Tangerang, August - October 2024. The results of this study for the stress level variable, the majority of the stress levels are mild (54.5%) and the pain variable is in the moderate category (90.9%). Based on statistical tests using the chi square correlation test, a significance level of p-value = 0.001 was obtained, so it can be concluded that there is a relationship between stress levels and pain in patients with dyspepsia in the Nusa Indah Room at Bhakti Asih Hospital, Tangerang, August - October 2024.